Multi-petal cyclamen flowers produced by AGAMOUS chimeric repressor expression - Tanaka, Yuri (Nature Publishing Group, 2013)
Cyclamen persicum (cyclamen) is a commercially valuable, winter-blooming perennial plant. We cloned two cyclamen orthologues of AGAMOUS (AG), CpAG1 and CpAG2, which are mainly expressed in the stamen and carpel, respectively. Cyclamen flowers have 5 petals, but expression of a chimeric repressor of CpAG1 (CpAG1-SRDX) caused stamens to convert into petals, resulting in a flower with 10 petals. By contrast, CpAG2-SRDX only caused incomplete formation of stamens and carpels. Expression in Arabidopsis thaliana showed similar effects on flower organ specification. Simultaneous expression of CpAG1-SRDX and CpAG2-SRDX in cyclamen induced rose-like, multi-petal flowers, a potentially valuable trait in commercial ornamental varieties. Expression of CpAG2-SRDX in a cyclamen mutant lacking expression of CpAG1 more effectively produced multi-petal flowers. Here, we controlled the number of petals in cyclamen by simple genetic engineering with a chimeric repressor. This strategy may be applicable useful for other ornamental plants with two distinct AG orthologues.